2021
DOI: 10.4269/ajtmh.21-0012
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic falciparum and Non-falciparum Malarial Parasitemia in Adult Volunteers with and without HIV-1 Coinfection in a Cohort Study in Western Kenya

Abstract: Asymptomatic malarial parasitemia represents the largest reservoir of infection and transmission, and the impact of coinfection with HIV-1 on this reservoir remains incompletely described. Accordingly, we sought to determine the prevalence of asymptomatic malarial parasitemia in Kombewa, Western Kenya, a region that is endemic for both malaria and HIV-1. A total of 1,762 dried blood spots were collected from asymptomatic adults in a cross-sectional study. The presence of parasitemia was first determined by a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…ovale positive samples (84.6%) were detected in the absence of other infecting parasite species. As in our previous cross sectional study ( Kifude et al., 2021 ), and like other previous studies within the region ( Howes et al., 2011 ), no P. vivax infections were detected in this population.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…ovale positive samples (84.6%) were detected in the absence of other infecting parasite species. As in our previous cross sectional study ( Kifude et al., 2021 ), and like other previous studies within the region ( Howes et al., 2011 ), no P. vivax infections were detected in this population.…”
Section: Resultssupporting
confidence: 88%
“…Malaria parasite transmission in this region occurs throughout the year with an estimated entomological inoculation rate for P. falciparum of 31.1 infectious bites per person per year ( Ndenga et al., 2006 ). Our previous cross-sectional surveillance study of adults from 2015 and 2018 revealed no significant differences in prevalence of parasitemia during the study period ( Kifude et al., 2021 ). In this study, enrollment of volunteers occurred between August 2018 and November 2019.…”
Section: Methodsmentioning
confidence: 75%
See 3 more Smart Citations